2010
DOI: 10.1371/journal.ppat.1000866
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Role for Macropinocytosis in Mediating Entry of the Two Forms of Vaccinia Virus into Dendritic Cells

Abstract: Vaccinia virus (VACV) is being developed as a recombinant viral vaccine vector for several key pathogens. Dendritic cells (DCs) are specialised antigen presenting cells that are crucial for the initiation of primary immune responses; however, the mechanisms of uptake of VACV by these cells are unclear. Therefore we examined the binding and entry of both the intracellular mature virus (MV) and extracellular enveloped virus (EV) forms of VACV into vesicular compartments of monocyte-derived DCs. Using a panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(87 citation statements)
references
References 76 publications
7
80
0
Order By: Relevance
“…We and others have previously shown that the vacuoles containing MVs also contain fluid markers such as dextran, and that they are devoid of transferrin, a cellular cargo molecule present in early and recycling endosomes 34, 35, 37, 38. This is consistent with reports indicating that classical endosomes and macropinosomes give rise to distinct transport vesicle populations 28.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We and others have previously shown that the vacuoles containing MVs also contain fluid markers such as dextran, and that they are devoid of transferrin, a cellular cargo molecule present in early and recycling endosomes 34, 35, 37, 38. This is consistent with reports indicating that classical endosomes and macropinosomes give rise to distinct transport vesicle populations 28.…”
Section: Discussionsupporting
confidence: 91%
“…VACV MVs and EVs initiate entry into host cells by triggering their own macropinocytic uptake 34, 35, 37, 38. About 30 min later, the viral core is delivered into the cytosol after fusion of the viral envelope with the limiting membrane of endocytic vacuoles 39, 46.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PAK activation contributes to the initial stages of actin remodeling and is later also involved in the macropinosome closure by activating C-terminal-binding protein-1/brefeldin A-ADP ribosylated substrate (CtBP-1 also known as BARS). 31,32,37,[76][77][78][79] Macropinocytic uptake has been reported for many viruses including, among others, poxviruses, Ebola virus, influenza virus, adenoviruses, herpesviruses and retroviruses. For example, several labs have reported on the role of Rho GTPases and macropinocytosis during vaccinia virus (VV) entry 27,37,77,78,80 For an extensive overview of the (subtle) differences in macropinocytic uptake between the different viruses we refer to a review by Mercer and Helenius.…”
Section: Macropinocytosismentioning
confidence: 99%